Development of an Hepatitis B pseudovirus system for safe and effective antiviral drug screening - Manasi Haval; Su Li; Guofang Zhang; Yang Li (The Microbe)
Hepatocellular carcinoma (HCC), a type of hepatic malignancy, is strongly linked to chronic hepatitis B virus (HBV) infection. HBV infection commonly advances asymptomatically for months; symptom onset may include nausea, fever, abdominal discomfort, jaundice, and anorexia. Existing therapies aim to alleviate symptoms, but no definitive cure exists. Prolonged exposure can lead to chronic infection, increasing the risk of HCC. Due to these risks, the infectivity of HBV-positive blood presents biosafety challenges for laboratory research on the virus. To address this, we seek to establish a refined HBV pseudovirus system using lentiviral backbone and utilizing an HBV surface antigen (HBsAg) plasmid, and the development of a NTCP-HepG2 cell line. The infectivity was measured using flow cytometry. This pseudo virus provides a non-infectious cell line for investigating HBV cellular uptake, surface receptor interactions, and prospective antiviral targets. By eliminating uncontrolled replication, our model enhances both research feasibility and laboratory safety.